Infratemporal Space Infection Following Maxillary Third Molar Extraction in an Uncontrolled Diabetic Patient - Ali Hossein Mesgarzadeh; Mohammad Ali Ghavimi; Gulşen Gok; Afsaneh Zarghami (Tabriz University of Medical Sciences, 2012)
Infratemporal space infection is a rare but serious sequel of odontogenic infection. The diagnosis is difficult due to non specific signs and symptoms. Diabetes mellitus as a definitive risk factor for odontogenic infections needs more consideration during clinical procedures. We report a case of an undiagnosed diabetic patient with isolated infratemporal space infection after tooth extraction with presentation of similar signs and symptoms of temporomandibular joint and muscle problem.